The Impact of PT Antam’s CSR Program on Income and Poverty in Tanjung Bunut - Mochammad Yunus Gerry Fitriadi; Fauzan Hamdani; Eka Puspita Sari (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose: This study aims to analyze the impact of the Corporate Social Responsibility (CSR) program of PT Antam, Bauxite Business Unit of West Kalimantan (UBPB Kalbar), particularly the Mamalam program (Manak Mandiri Man alam, meaning “we are self-reliant with nature”), on improving household income and reducing poverty among communities surrounding the company’s operational area. Methodology: The research employed a descriptive quantitative approach using primary data collected through questionnaires distributed to 30 members of the Mamalam Embaloh Permai farmer group in Tanjung Bunut Village, Sanggau Regency, and secondary data obtained from company documents and relevant literature. Result: The results show a significant increase in household income from IDR 2,031,667 to IDR 4,901,667 per month after joining the program, with 87% of households above the national poverty line (BPS) and 53% above the World Bank threshold. Findings: These findings indicate that sustainable agribusiness-based CSR effectively improves community welfare and strengthens local economic self-reliance. Novelty: The novelty of this research lies in combining household economic analysis with global poverty indicators to assess CSR effectiveness in the mining sector. Originality: Its originality is reflected in the focus on tangible economic impacts of community-based empowerment programs. Conclusion: In conclusion, the Mamalam program has proven effective as a sustainable CSR model that contributes to the economic, social, and environmental development of surrounding communities. Type of Paper: This paper is categorized as a research article.